International Standards of Implementing Mediation within Criminal Proceedings and the State of Its Realization in Ukraine - T. H. Fomina (Bulletin of Kharkiv National University of Internal Affairs)
International standards for mediation in criminal proceedings have been defined; the process of development of the institution of mediation in criminal proceedings in Ukraine has been characterized; propositions on improving the procedure for mediation in criminal proceedings have been expressed.